Performance and efficiency analysis of a new annular cooler for waste heat recovery in sintering process - Yan Peng; Yaodong Zhang; Kun Jiao; Jian Cui; Hengjian Jin; Zhen Li; Naitao Guo; Huixia Wang; Xinru Zhang; Lin Lin; Zeyi Jiang; Xinxin Zhang (Case Studies in Thermal Engineering)
Currently, the waste heat recovery rate in the sintering process is less than 40 %. Developing annular coolers with high efficiency is critical for waste heat recovery in sintering processes. Herein, we studied the performance and efficiency of a new annular cooler system that connects two cooling beds in series, by developing a mathematical model. The influence of four parameters on the performance and exergy efficiency of this new process was further studied, including the temperature of cooling gas (Tg, in4), the temperature of sinter entering annular coolers (Ts, in), the movement speed of sinter bed (Vsinter bed), and the height of sinter bed (Hsinter bed). The results indicate that the recovered exergy of the new process (300.72 MJ/t·sinter) significantly increases compared to the conventional process (186.51 MJ/t·sinter), with the exergy efficiency rising to 72.34 %, which is 1.6 times higher than that of the conventional process (44.87 %). The internal exergy loss in the new process is reduced by 4.01 MJ per ton of sinter compared to the conventional process. Moreover, Ts, in has a significant effect on the recovered exergy of hot gas, while, Hsinter bed notably influences the exergy efficiency of the new process. The study provides important theoretical insights to develop new annular coolers for improving waste heat recovery in the sintering process.